1 - Global Trends in Higher Education Reform: What Lessons for Nigeria? - Adesina, Jimi (Journal of Higher Education in Africa, 2006)
The crisis that engulfed the higher education sector in many developing countries from the mid-1970s in many ways epitomised a much wider socio-economic and political crisis. In much of Africa the balance of payment crisis compounded an uneasy relationship between the rulers and academia. However, addressing the cri- sis in the 1980s was defined by the emergent neo-liberal mindset. It was also an ideological posture that saw the academy as a domain of a ‘leftist leisure class’ that needed market discipline. Education as a public good was replaced by a commodity logic. The impact of the neo-liberal orthodoxy on the higher education sector, how- ever, varied widely across counties. In countries whose education policy came un- der the direct control of the Bretton Woods institutions, the orthodoxy drove policy as close to its ideological posturing as possible. In many developing countries commodification of access has impacted harshly on research activities in the higher education sector, reversing earlier achievements at endogeneity. In some countries, including Nigeria, the persistent anti-intellectualism of those in power has intensi- fied the broader crisis. In this paper, I argue that this contrasts sharply with the domestic experience of the Organisation for Economic Cooperation and Develop- ment (OECD) countries in their higher education sectors and the public commit- ment to research and development. What lessons are there for higher education reform in Nigeria? Firstly, in spite of the neo-liberal claims, successful countries show strong commitment to education as a public good and tend to invest heavily in their higher education sector, especially in endogenous research and development. The second point is that experiments with the commodity approach in both its provisioning of skilled human resources and internal relations have proved to be counter-productive. Thirdly, in situations of prolonged decline and decay, what needs rebuilding is more than just the infrastructure but also the ethos and ethics of academia.